Belgium : 2015 Article IV Consultation-Staff Report; and Press Release. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Belgian economy has shown considerable resilience but the outlook is weighed down by weak demand in Europe. Healthy private balance sheets, integration with Germany, and employment support schemes have helped sustain employment and economic activity. However, output is still well below potential and with, subdued growth prospects, job creation remains insufficient. Fiscal adjustment is expected to resume after a pause in 2014. The pace of adjustment targeted by the authorities for 2015-16 is appropriate given the level of debt and related risks.